Registration of the TCAP FAC‐WIN6 Barley Panel for Genomewide Association Studies. Issue 3 (6th August 2015) - Belcher, Araby R.; Graebner, Ryan C.; Cuesta-Marcos, Alfonso; Fisk, Scott; Filichkin, Tanya; Smith, Kevin P.; Blake, Victoria C.; Hayes, Patrick M.
Abstract : Facultative/winter six‐row malting barley is a distinct elite germplasm pool and a valuable resource that may prove useful in meeting the challenges of climate change. To preserve its diversity and make it accessible to the research and agricultural communities, the Oregon State University and University of Minnesota barley breeding programs are publicly releasing their winter/facultative six‐row malt advanced lines named the TCAP FAC‐WIN6 (MP‐1, NSL 512632 MAP), which also function as a genomewide association studies (GWAS) panel. The FAC‐WIN6 contains 296 lines—180 facultative and 116 winter—selected for disease resistance, malt quality, and general agronomic performance. To date, all lines have data for 6892 single nucleotide polymorphism (SNP) markers and phenotypic data from six experiments (representing 3 yr, eight locations), including traits such as malt quality, disease resistance, nitrogen use efficiency, and winter hardiness. The FAC‐WIN6 is one of 24 barley and wheat mapping panels and populations from the USDA‐ARS Triticeae Coordinated Agricultural Project (TCAP). As such, all of the TCAP FAC‐WIN6 genotypic and phenotypic data can be freely downloaded from the TCAP's online database, T3 (http://triticeaetoolbox.org/barley /). Preliminary GWAS have identified novel loci for wort β‐glucan, low temperature tolerance, and disease resistance. Given these results, the FAC‐WIN6 is a singular resource both for future winter six‐row barley breeding and for identifying and deploying genes for key barley traits in all backgrounds.